Study on optimization of pouring time for late poured band - Xie, Liang; Tang, Bin; Liu, Shaoqing; Gong, Yanxia; Cheng, Xunchao (Frontiers in Built Environment, 2023)
The setting of the late poured band is an effective measure to control the differential settlement and the stress concentration of the foundation. However, the lag of the pouring time of the late poured band will also bring adverse effects to the construction process. Taking a large commercial complex as an example, Midas GTS NX finite element software is used for the overall foundation modeling, and the collaborative calculation of settlement is carried out by adjusting the composite foundation scheme. The calculation results of conventional codes are compared and analyzed, and the scheme is verified and optimized. Then, the variation value of differential settlement on both sides of the late poured band with loading is studied by simulating the graded loading of each area in the whole process of construction. By comparing the variation value of differential settlement and the calculation value of differential deformation that the stiffness of the late poured band can resist and the limit value of codes, the time node of late poured band pouring in advance can be obtained, and finally the influence of early closure of the late poured band on the collaborative settlement of the foundation is verified and calculated. This method can verify and optimize the design scheme of composite foundation and save the pouring time of the late poured band. The experience and achievements so made can be used as a reference for similar projects.